2021
DOI: 10.1002/jpen.2264
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk: New chronic care models

Abstract: Cardiometabolic risk factors, and the chronic cardiovascular diseases (CVDs) that result from them, are highly prevalent in the US and amenable to clinical nutrition interventions. This creates an urgency to develop comprehensive care models that incorporate prevention-based actions by improving lifestyle routines. Such care models should account for social determinants of health, ethnocultural variables, and challenges to sustainability. The relevance of these newly designed chronic care models is to inform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
0
12
0
2
Order By: Relevance
“…Our subgroup analyses confirm that significant effects on ccIMT may be more easily demonstrated in individuals with higher baseline ccIMT (21) , and such higher ccIMT values are more likely to be present in study samples of individuals with confirmed CVD risk factors such as hypercholesterolaemia (31) or diabetes (23,35) . Nevertheless, it is of high public health relevance to develop tools (such as our intervention programme) which already initiate CVD prevention measures in individuals who are still at low to moderate CVD risk (37) . Consequently, it appears justifiable to conduct further lifestyle/dietary interventions assessing ccIMT change in generally healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Our subgroup analyses confirm that significant effects on ccIMT may be more easily demonstrated in individuals with higher baseline ccIMT (21) , and such higher ccIMT values are more likely to be present in study samples of individuals with confirmed CVD risk factors such as hypercholesterolaemia (31) or diabetes (23,35) . Nevertheless, it is of high public health relevance to develop tools (such as our intervention programme) which already initiate CVD prevention measures in individuals who are still at low to moderate CVD risk (37) . Consequently, it appears justifiable to conduct further lifestyle/dietary interventions assessing ccIMT change in generally healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, malnutrition has been shown to persist 30 days post-COVID-19 discharge ( 86 ). As such, patients with COVID-19, especially those with diabetes, may require tailored medical nutrition therapy to improve short- and long-term COVID-19 outcomes ( 71 , 72 , 87 , 88 ).…”
Section: Edge 2: Covid-19 and Malnutritionmentioning
confidence: 99%
“…When other metabolic drivers (e.g., abnormal adiposity [adiposity-based chronic disease; ABCD], hypertension [hypertension-based chronic disease; HBCD], and dyslipidemia [lipid-based chronic disease; LBCD] are configured along the 4 stages, a 2 × 2 matrix arises and depicts the 2-dimensional CMBCD framework. 29,32 In the third dimension, each stage and driver (represented by each cell of the 2 × 2 CMBCD matrix) is populated by SDOH and other ethnocultural factors to improve precision of preventive actions and optimize outcomes (Figure 3). Implementing this model in the daily routine clinical practice implies the staging of the patient’s individual risk for each biological driver (adiposity, dysglycemia, hypertension, dyslipidemia) and the incorporation of social determinants to specify the lifestyle recommendations.
Figure 3.The transcultural Cardiometabolic-Based Chronic Disease (tCMBCD) model.
…”
Section: Lifestyle Medicine At Ldhmentioning
confidence: 99%
“…In the first dimension, the 4 stages are mapped to specific prevention modalities: 1 (Risk-primordial prevention of risk development and progression), 2 (Predisease-primary prevention of disease), 3 (Disease-secondary prevention of complications), and 4 (Complications-tertiary prevention of suffering and mortality); each stage is also subject to quaternary prevention (the avoidance of overmedicalization and unethical behavior). 29,31,32 In the second dimension, individual metabolic drivers are considered as progressing along these 4 stages. For example, the dysglycemia-based chronic disease (DBCD) model constitutes a new way to approach diabetes prevention and management: stage 1 is insulin resistance, stage 2 prediabetes, stage 3 T2D, and stage 4 cardiovascular complications.…”
Section: Codification Of These Various Sequential Processes Facilitat...mentioning
confidence: 99%